1983
DOI: 10.1161/01.str.14.6.911
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarction of the basal ganglia due to embolism from the heart.

Abstract: SUMMARY We studied 8 patients with cerebral infarction in the deep territory of the middle cerebral artery (MCA). All patients had a definite cardiac source of emboli and no known factors for thrombosis. Mixed sensory and motor deficit was found in all but one patient and CT scan showed larger lesions than usually reported in lacunar infarcts. Contrast enhancement was seen in all cases in which CT scan was performed in the second or third week. It is concluded that embolic infarcts in deep cerebral territory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 19 publications
0
25
2
1
Order By: Relevance
“…Although controversy surrounds the question of whether large artery atherosclerosis or a cardioembolic source are coincidental [9,[24][25][26][27][28][29][30][31][32][33][34][35][36] or causative [11,[27][28][29] in patients with small deep infarcts, the documentation of mechanisms of stroke in patients with deep infarcts is important because different therapeutic approaches may be required, depending on their pathogenesis [17,22,30] .…”
Section: Nonlacunar Mechanisms In Developing Small Deep Infarctsmentioning
confidence: 99%
“…Although controversy surrounds the question of whether large artery atherosclerosis or a cardioembolic source are coincidental [9,[24][25][26][27][28][29][30][31][32][33][34][35][36] or causative [11,[27][28][29] in patients with small deep infarcts, the documentation of mechanisms of stroke in patients with deep infarcts is important because different therapeutic approaches may be required, depending on their pathogenesis [17,22,30] .…”
Section: Nonlacunar Mechanisms In Developing Small Deep Infarctsmentioning
confidence: 99%
“…Gorsselink et al 132 reported 12% of cases with small deep infarcts as having potential cardioembolic sources, similar to the 10% in the Harvard study, 2 though there were no such cases in Weisberg's study. 40 Santamaria et al 53 reported a series of patients with basal ganglia infarcts and a variety of cardiac conditions that frequently cause embolism. They noted that the clinical abnormalities were usually more extensive than the described lacunar syndromes, though three cases appear to have had sensorimotor strokes.…”
Section: Risk Factor Analysismentioning
confidence: 99%
“…2 -514 - 17 Treatment of these extracranial lesions is controversial, especially since such potential sources of emboli might in fact be coincidental. 18 -20 It is unresolved whether carotid endarterectomy should be undertaken in patients who have had a transient ischemic attack or a minor stroke distal to an atherosclerotic lesion in the extracranial course of that artery, even if the location and size of the infarct are disregarded.…”
Section: Acunar Infarction Constitutes Between 10%mentioning
confidence: 99%